Peter Pan de Monteiro Lobato: entre capas e ilustrações, um olhar nos protocolos de leitura - Lima, Joaes Cabral de (2020)
The reading protocols, in their various aspects and uses, which cover the structure of the book concerning its entire editorial graphic project, are used as anticipatory elements of the text, due to its narrative load, in the same way that they also guide reading, explaining certain items; organizing your order; summarizing chapters, in addition to, in the case of illustration, establishing a discursive relationship with the text itself, as evidenced by CARVALHO (2008), CAVALCANTE (2010) and ARANTES (2019). Bearing in mind the importance of reading protocols, which although little studied in the academic environment, but evidenced by theorists in their studies about reading, such as CHARTIER (1990), SCHOLES (1989), ROSA (2016), MARTINS (1989) , BASTIANETTO (2005) among others, this dissertation aims to evaluate the several changes that occurred over time in the covers and internal illustrations of Peter Pan’s adaptation, performed by Monteiro Lobato in 1930, through the reading protocols and the cultural history itself. In addition to this, we highlight the many adapted and translated editions that were carried out by different Brazilian publishers. In order to carry out this work, we started from a methodology centered on bibliographic research from dissertations, theses and Lobato's own children's works, in particular, the various editions of Peter Pan’s adaptation. A biographical research by Monteiro Lobato was also necessary, given its relevance in the construction of the Brazilian publishing market in the first decades of the 20th century and his contribution as an author and innovator in the field of Brazilian children's literature. In this way we were able to identify significant changes both in the graphic design of the many editions of the adaptation made by Lobato, as well as in relation to textual elements.